2005
DOI: 10.1096/fj.04-2916fje
|View full text |Cite
|
Sign up to set email alerts
|

Adult neural stem cell cycling in vivo requires thyroid hormone and its alpha receptor

Abstract: Thyroid hormones (TH) are essential for brain development. However, information on if and how this key endocrine factor affects adult neurogenesis is fragmentary. We thus investigated the effects of TH on proliferation and apoptosis of stem cells in the subventricular zone (SVZ), as well as on migration of transgene-tagged neuroblasts out of the stem cell niche. Hypothyroidism significantly reduced all three of these processes, inhibiting generation of new cells. To determine the mechanisms relaying TH action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 41 publications
6
116
2
Order By: Relevance
“…Other in vivo studies show that TH could reverse impaired hippocampal neurogenesis during development 53 and in the adult SVZ. 26 Lemkine et al 26 found that TH influence precursor cell proliferation in the SVZ, using Ki67 and phosphorylated histone H3 as proliferation markers. The effect was not observed when BrdU incorporation was used, which led the authors to propose that hypothyroidism increased the number of progenitors in the resting state in the SVZ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other in vivo studies show that TH could reverse impaired hippocampal neurogenesis during development 53 and in the adult SVZ. 26 Lemkine et al 26 found that TH influence precursor cell proliferation in the SVZ, using Ki67 and phosphorylated histone H3 as proliferation markers. The effect was not observed when BrdU incorporation was used, which led the authors to propose that hypothyroidism increased the number of progenitors in the resting state in the SVZ.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] TH action is mediated through T3 nuclear receptors, and T3 receptor deficiency or mutations also alter adult hippocampal structure and hippocampus-dependent behavior. 23,24 Very recently, TH have been implicated in adult neurogenesis, [25][26][27][28] but little is known on the functional consequences of TH actions on proliferation of neuronal progenitors.…”
Section: Introductionmentioning
confidence: 99%
“…These data strongly suggest a potential therapeutic use of THs in Alzheimer's disease. Adult neural stem cells of the subventricular zone (SVZ) in mouse also require THs and TRα1 function (Lemkine et al, 2005). In these cells in vivo, THs-TRα1 likely act to inhibit the expression of c-Myc and cyclin D1, inducing their exit from the cell cycle.…”
Section: Postnatal Neurogenesismentioning
confidence: 99%
“…The regulation of neurotransmitter release in the hippocampus was also influenced by the presence of thyroid hormones; electrophysiological studies of short-term synaptic plasticity showed that facilitation of paired pulse patterns were found to be extremely modified in animals with hypothyroidism, this condition being reversible with the administration of thyroid hormones [34]. Investigations on cell proliferation in the sub-ventricular zone (SVZ) of the hippocampus also demonstrated that T3 and its receptor alpha (TRα) play an important role in neurogenesis in this region [35]. Effects on extracellular matrix synthesis were also observed in cerebellum, since the absence of thyroid hormones delay laminin expression [36] [37], and their levels were 35% lower than control animals (Farwell et al, 1995 (Figure 2).…”
Section: T3 and T4 Effects In Nervous System Developmentmentioning
confidence: 99%